Personal Learning Services and Immersive Learning in Art Design to Enhance Indonesian Education - Pramono, Andy; Dewi Puspasari, Betty (KnE Social Sciences, 2023)
Indonesia was one of the countries that successfully survived the COVID-19 pandemic. The pandemic has provided good lessons, especially in the education sector, and ithas provided new ways of overcoming problems in education, especially in art and design. In this paper, I will share experiences related to Personal Learning Services based on gamification and the implementation of immersive learning based on Augmented Reality, which was developed at the Department of Art and Design at theState University of Malang in Indonesia. This research was developed for primary education students in Indonesia, especially in Malang City, East Java. The contribution forthis article was as follows: 1) developed some research to solve the learning problem impact of COVID-19; 2) with the software, media, and game specialization group in the art design department conducted several studies in the form of Personal Learning Services and immersive learning. In the discussion of Personal Learning Services based on gamification, the study aims to improve the quality of children’s characters by displaying background designs in several main locations in Malang. This research includes several minigames that attempt to increase children’s discipline, routine, and consistency. Related to implementing immersive learning based on Augmented Reality, is research to introduce characters in wayang panji to children. This study develops Augmented Reality technology without markers to make it easier for users to learn without fear of losing the marker, which has been a problem in AR. This research, acccording to the survey with the statistical tests result shows that it is a feasible solution to apply to the learning process. Keywords: learning media, personal learning services, gamification, immersive learning, augmented reality